Mitigasi Kesadaran Diri terhadap Kelestarian Alam - Linda Happy Silalahi; Yuniar Fitriani; Jelita Liona Siagian (Yayasan Aya Sophia Indonesia, 2023)
This study targets the natural environment which continues to experience damage to the point of causing negative effects due to continuous and ongoing damage. In this study, the authors used a descriptive qualitative method with the listening and note technique, namely by listening and recording narratives orally. The main source of information for this study is Jawara H. Chaeruddin's YouTube podcast video at TED X Tangsel entitled Wisdom of Nature. The results of this study conclude that according to the Sustainable Development Goals, Indonesia is the second largest recycler of plastic waste in the world, after China. This greatly affects the extraordinary natural beauty of Indonesia and damages various ecosystems, so that the proposed technological solutions cannot solve the problem at all, and the problem of damage to the natural environment has not been resolved. This research also requires efforts to protect and manage the natural environment that is inclusive, sustainable, and coherent. This means that accepting the ecological values contained in local wisdom can help make people aware of how to treat the natural environment so that they can develop good ecological attitudes.